Pengaruh Komunikasi Organisasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada Cv. Wahana Sukses Makmur Kota Tangerang Selatan - Fadila Choirun Nisa; Udin Saprudin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study is to determine the effect of organizational communication and the physical work environment on employee performance at CV Wahana Sukses Makmur. The research method used is a quantitative method. The sampling technique employed is saturated sampling, involving 63 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing with the assistance of SPSS version 30. The results of this study indicate that organizational communication has a significant effect on employee performance, with a coefficient of determination of 52.5%, and the hypothesis test shows that the calculated t-value is greater than the t-table value (8.214 > 2.000). The physical work environment has a significant effect on employee performance, with a coefficient of determination of 48.8%, and the hypothesis test shows that the calculated t-value is greater than the t-table value (7.618 > 2.000). Simultaneously, organizational communication and the physical work environment have a significant effect on employee performance, with the regression equation Y = 2.565 + 0.563X₁ + 0.297X₂. The coefficient of determination is 55.7%, while the remaining 44.3% is influenced by other factors not examined in this study. The hypothesis test shows that the calculated F-value is greater than the F-table value (37.783 > 2.758).